A study on patient satisfaction with psychiatric services - Holikatti, Prabhakar C. (Medknow Publications & Media Pvt Ltd, 2012)
CONTEXT: Patient satisfaction with psychiatric services is an important construct, which influences multiple areas including treatment adherance and outcome. There is paucity of studies from India in this area. AIMS: To measure satisfaction of psychiatric outpatients of Mental Health Institute, Cuttack, and to assess the relationship between demographic and clinical variables with different domains of patient satisfaction. SETTINGS AND DESIGN: In a cross-sectional study, patients of age 18-60 years receiving treatment for at least six months from outpatient department of Mental Health Institute, SCB Medical College, Cuttack, were assessed. MATERIALS AND METHODS: Participants (n=60) were selected randomly. Satisfaction was assessed by Patient Satisfaction Questionnaire–18 (PSQ-18) and the diagnoses were based on the Diagnostic and Statistical Manual-IV-TR. Severity of psychiatric disorder was measured using Clinical Global Impression-severity scale. The functioning level was assessed by Global Assessment of Functioning. STATISTICAL ANALYSIS: Continuous variables compared using independent t-test or analysis of variance. RESULTS: Diagnostic break-up of the patients included anxiety disorder (36.6%), major depressive disorder (30.0%), bipolar disorder (16.6%), and schizophrenia (16.6%). Greatest level of satisfaction was noted in interpersonal aspects (71.4%) and time spent with doctors (62.4%). General satisfaction level was a little over 50% (57%). Differences between composite scores of PSQ-18 in the diagnostic categories were statistically significant; patients with depression had the highest score followed by those with anxiety disorder, bipolar, and the least was with schizophrenia patients. There was variability among the demographic and clinical groups regarding the various subscale score of PSQ-18. CONCLUSIONS: Satisfaction of psychiatric outpatients was observed to be different in various clinical and demographic groups and across many domains of satisfaction.